Influence of driving and parasitic parameters on the switching behaviors of the SiC MOSFET - Zhang, Shangzhou (Frontiers in Energy Research, 2023)
The SiC MOSFET has lower conduction loss and switching loss than the Si IGBT, which helps to improve the efficiency and power density of the converter, especially for those having strict requirements for volume and weight, for example, electrical vehicles (EVs), on-board chargers (OBCs), and traction drive systems (TDS). However, the faster switching speed will cause overshoot and oscillation problems, which will affect the efficiency and security of the SiC devices and power electronic systems. For the SiC MOSFET to be better used, combining a theoretical analysis, the double-pulse test platform is built. The controllable principles of SiC MOSFETs are validated. The turn-on and turn-off delay, switching delay, switching di/dt, switching du/dt, switching overshoot, and switching loss of SiC MOSFETs under different driving and parasitic parameters are explored. Finally, some valuable suggestions for designing are proposed for a better application of the SiC MOSFET.